2005
DOI: 10.4049/jimmunol.174.10.6322
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase R Mediates Intestinal Epithelial Gene Remodeling in Response to Double-Stranded RNA and Live Rotavirus

Abstract: As sentinels of host defense, intestinal epithelial cells respond to the viral pathogen rotavirus by activating a gene expression that promotes immune cell recruitment and activation. We hypothesized that epithelial sensing of rotavirus might target dsRNA, which can be detected by TLR3 or protein kinase R (PKR). Accordingly, we observed that synthetic dsRNA, polyinosinic acid:cytidylic acid (poly(I:C)), potently induced gene remodeling in model intestinal epithelia with the specific pattern of expressed genes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 60 publications
1
41
0
Order By: Relevance
“…Although PKR signaling through NF-B may have a role in the poly(I:C) stimulated IL-8 response, those studies did not assess type I IFN expression. Moreover, the specificity of inhibition by 2-AP for PKR in those studies was not confirmed using specific genetic approaches (46). Whereas, 2-AP inhibited poly(I:C) stimulated type I IFN production, we also found that 2-AP inhibition was not specific for PKR Thus, in addition to PKR, 2-AP also inhibited STAT1 and IRF3 phosphorylation that are key in the activation of the IFN pathway (data not shown), and others have previously reported that 2-AP inhibited leptin induced STAT3, ERK, and JNK activation, independently of PKR (47).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although PKR signaling through NF-B may have a role in the poly(I:C) stimulated IL-8 response, those studies did not assess type I IFN expression. Moreover, the specificity of inhibition by 2-AP for PKR in those studies was not confirmed using specific genetic approaches (46). Whereas, 2-AP inhibited poly(I:C) stimulated type I IFN production, we also found that 2-AP inhibition was not specific for PKR Thus, in addition to PKR, 2-AP also inhibited STAT1 and IRF3 phosphorylation that are key in the activation of the IFN pathway (data not shown), and others have previously reported that 2-AP inhibited leptin induced STAT3, ERK, and JNK activation, independently of PKR (47).…”
Section: Discussionmentioning
confidence: 83%
“…Poly(I:C) was reported to up-regulate IL-8 mRNA in the human IEC line T84 in the absence of an added membrane permeant, by signaling through PKR as determined using pharmacological inhibitors of PKR (e.g., 2-AP) (46). Although PKR signaling through NF-B may have a role in the poly(I:C) stimulated IL-8 response, those studies did not assess type I IFN expression.…”
Section: Discussionmentioning
confidence: 99%
“…Although NF-B activation following stimulation with poly(I:C) has also been observed in other cells of the epithelial lineage, such as in human respiratory (46 -49), reproductive (50), uterine (51), and intestinal (52,53) epithelium, this has been generally attributed to the expression and function of TLR3. Apart from TLR3-dependent NF-B activation after dsRNA stimulation, IRF3 signals resulting in type I IFN production have also been demonstrated as a consequence of TLR3 ligand binding in normal human keratinocytes using a model that did not integrate the combined function of PKR, RIG-I (54), or MDA5 (45).…”
Section: Discussionmentioning
confidence: 99%
“…However, Lcn2 was originally discovered as an early response gene, induced to high levels in growth-arrested murine kidney cells following infection with simian virus 40 (SV40) (30). More recently, rhesus rotavirus infection of human epithelial cells (31) and human papillomavirus infection of keratinocytes (32) were also shown to induce Lcn2. Despite these associations of Lcn2 with viral infection of cells in vitro, little is known concerning the regulation of Lcn2 gene expression and the function of this factor in the host response to viral infection in vivo.…”
Section: Discussionmentioning
confidence: 99%